Borders between Europe and China: Why do Europeans (mis)understand Chinese culture? - Juzefovič, Agnieška (Creativity Studies, 2009)
The article goes deeper into the dialogue of inter‐cultural Chinese and Western civilizations. It is analyzed how the Westerners perceive Chinese civilization and culture. The methods used here are the comparative and hermeneutical ones, as it is aimed to compare two different cultures and to penetrate the problems of understanding. The problems of understanding are not new, they have been analyzed a lot. The novelty of this article is determined by the fact that these problems are investigated in the outlooks of the understanding of Chinese culture and, especially, landscape aesthetics. Thus, the objects of this research are an inter‐civilization dialogue and an inter‐civilization conflict. The author of this article discusses why often it is difficult to develop a meaningful cultural dialogue between China and Europe, why this dialogue is relevant and how it could help Europeans to understand the Other and themselves. The idea presented in the article is that the Westerners are often mislead by a Chinese traditionalism, which is ambivalent and closely related to creativity and constant change, thus it should not be identified with stagnation and dogmatism. One more aspect of Chinese culture, which Europeans find difficult to understand, is its unity, which has deep philosophical implications and ability to connect the opposites. The author assumes that Western‐Eastern Europe has many distinctive features, but the inhabitants of this region view classical Chinese culture and an art in a similar way as the inhabitants of the rest of Europe: all Europeans have similar stereotypes and difficulties to understand separate aspects. This allows us to speak about a common European approach.Europos ir Kinijos ribos: kodėl mums sunku suprasti kinų kultūrą?Santrauka. Straipsnyje gilinamasi į tarpkultūrinį kinų ir Vakarų civilizacijų dialogą. Nagrinėjama, kaip vakariečiai suvokia kinų civilizaciją ir kultūrą. Čia taikomi komparatyvistinis ir hermeneutinis metodai, nes siekiama palyginti dvi skirtingas kultūras ir įžvelgti supratimo problemų. Supratimo problemos nėra naujos, jau yra daug tyrinėtos, bet šio straipsnio naujumą lemia tai, kad jos gvildenamos kinų kultūros ir ypač kinų peizažinės estetikos supratimo perspektyvoje. Todėl šio tyrimo objektai yra tarpcivilizacinis dialogas ir tarpcivilizacinis konfliktas. Straipsnio autorė svarsto, kodėl dažnai sunkiai sekasi plėtoti prasmingą kultūrinį Kinijos ir Europos dialogą, kodėl jis yra aktualus bei kaip jis galėtų padėti europiečiams suprasti Kitą ir save patį. Išsakoma mintis, kad vakariečius dažnai klaidina kinų tradicionalizmas, kuris yra labai ambivalentiškas bei glaudžiai susijęs su kūrybingumu ir nuolatine kaita, todėl neturėtų būti tapatinamas su sąstingiu ir dogmatizmu. Kitas europiečiams sunkiai suprantamas kinų kultūros aspektas yra gilias filosofines potekstes turintis jos vientisumas, gebėjimas jungti priešybes. Autorės manymu, šiaurės rytų Europa turi daug savitų bruožų, tačiau šio krašto gyventojai į klasikinę kinų kultūrą ir dailę žvelgia panašiai kaip ir likusios Europos dalies gyventojai – visiems europiečiams būdingi panašūs stereotipai ir dėl jų kylantys sunkumai suprasti paskirus aspektus. Tai leidžia kalbėti apie europiečiams bendrą pasaulėžiūrą.Reikšminiai žodžiai: kinų kultūra, kitoniškumas, tarpcivilizacinis dialogas, supratimo problemos, peizažinė estetika.First Published Online: 14 Oct 2010